TINJAUAN HUKUM ISLAM TERHADAP JUAL BELI BIBIT IKAN LELE DENGAN SISTEM SAMPEL (Studi Kasus di Desa Madusari Kecamatan Siman Ponorogo) - Alkusnaini, Muhammad Irsyad; Kadenun, Kadenun; Fathoni, Khoirul (Social Science Academic, 2023)
Many residents of Madusari Village, Siman Ponorogo District, are engaged in the business of buying and selling catfish seeds, because according to them selling and raising catfish seeds is capable of making a profit and the yield is sufficient to meet their daily needs. Buying and selling catfish seeds in Madusari Village, Siman District uses a sample system. The sample system, namely the first scale, is used as a reference for the next scale. Based on the background above, the researcher took the formulation of the problem about how to buy and sell catfish seeds using the sample system in Madusari Village, Siman Ponorogo sub-district. What is the review of Islamic Law on the Mechanism of Buying and Selling Catfish Seeds with the System in Madusari Village, Siman Ponorogo District. The steps in the data collection technique are interviews, observation, and documentation. The mechanism for buying and selling catfish fingerlings uses a sample system in Madusari Village, Siman Ponorogo District, which is carried out by grouping the size of the fish seeds using the previous grading bucket, then weighing them on a digital scale weighing 1 ounce and it is known that in 1 ounce the average number is 15 fish, for The second scale and so on do not count the number of catfish fingerlings, even though between the first scale and so on the number of catfish fingerlings is not the same, but both parties are mutually willing, and after the calculation is complete, one ounce is added in each transaction..